IFPRI Malawi Monthly Maize Market Report, September 2025 - International Food Policy Research Institute; Benson, Anderson (International Food Policy Research Institute, 2025)
Highlights Retail prices of maize were relatively stable in September. National price stability concealed significant market-level variations in maize prices. Imports continued dominating cross-border trade in maize.